Exploring EFL Students’ Perceptions of Memes As Supplementary Media for English Vocabulary Learning - Hanna Luthfia Tavania; Zuhad Ahmad (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Vocabulary learning in English as a Foreign Language (EFL) contexts is often associated with repetitive memorization and limited engagement. Although memes have been examined as tools for vocabulary acquisition and retention, less attention has been given to how students perceive their role in incidental and informal digital learning. This qualitative descriptive study explored EFL students’ perceptions of memes as supplementary media for English vocabulary learning. Seven sixth-semester students from the English Education Study Program at FKIP UHAMKA were selected through purposive sampling. Data were collected through semi-structured Zoom interviews and analyzed through transcription, repeated reading, manual coding, category development, theme development, interpretation, and member checking. The findings revealed that memes provided incidental exposure to unfamiliar vocabulary, supported meaning recognition through visual and contextual cues, and increased enjoyment, curiosity, and engagement. Participants also associated humorous and relatable contexts with vocabulary retention. However, they noted that slang, wordplay, cultural references, ambiguous meanings, and inappropriate language could limit the educational value of memes. The study contributes to understanding how incidental vocabulary learning, multimodal input, and learner engagement interact in informal digital environments. Memes are therefore most appropriate as carefully selected supplementary materials alongside structured vocabulary instruction.